2008
DOI: 10.1080/17457300801972221
|View full text |Cite
|
Sign up to set email alerts
|

Young drivers at railway crossings: an exploration of risk perception and target behaviours for intervention

Abstract: Research into motorist understanding and behaviour at railway crossings is currently limited in Australia, despite 74 fatalities being recorded due to collisions between trains and motor vehicles from 1997 to 2002. The present study explored the knowledge, attitudes and self-reported behaviour of younger drivers aged 17-24 years, as an 'at risk' group. The objective of this study was to develop a formative understanding of the nature and underlying beliefs of younger drivers' behaviours at railway crossings, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Intentional non-compliance with RLX signals occurs when drivers detect the train and the RLX warnings and understand the meaning of the warnings, but will nevertheless intentionally cross. A propensity to engage in risk taking or sensation seeking behaviour and a low perception of risk have both been found to contribute to intentional non-compliance at RLXs (Davey et al, 2008;Witte and Donohue, 2000). Experimental evidence suggests that illusory size-speed biases, which lead road users to underestimate the speed of large vehicles such as trains, could also contribute to intentional non-compliance (Clark et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Intentional non-compliance with RLX signals occurs when drivers detect the train and the RLX warnings and understand the meaning of the warnings, but will nevertheless intentionally cross. A propensity to engage in risk taking or sensation seeking behaviour and a low perception of risk have both been found to contribute to intentional non-compliance at RLXs (Davey et al, 2008;Witte and Donohue, 2000). Experimental evidence suggests that illusory size-speed biases, which lead road users to underestimate the speed of large vehicles such as trains, could also contribute to intentional non-compliance (Clark et al, 2013).…”
Section: Introductionmentioning
confidence: 96%
“…Studies have reported differences in intentional and unintentional violations at railroad crossings. Intentional violations may also be a result of drivers having a low perception of risk (12) or being in a hurry (13,14).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ranney et al, [12] To some extent, one of the main causes of road accident is drivers' attitude. The term 'attitude' itself means an individual desire to behave properly or poorly in relation to safety [4]. In the matter of attitude, the use of seat belts while driving influences the probability of accidents and injury [1].…”
Section: Defining Perception Practice and Attitudementioning
confidence: 99%